NEUROMYELITIS OPTICA SPECTRUM DISORDER AND CMV RETINITIS: A CASE REPORT. (29th November 2012) - George, J; Kitley, J; Leite, MI; Elston, JS; Matthews, BN; Cortes, N; Donati, M; Jones, N; Palace, JA
Abstract : Case summary: A 64-year-old lady presented with aquaporin-4 antibody positive transverse myelitis. Azathioprine and oral steroids were commenced. Fifteen months later, she presented with a painless unilateral visual field deficit with afferent pupillary defect and a diagnosis of right retrobulbar optic neuritis was made and treated with increased immunosuppressive therapy. Three months later CMV retinitis was diagnosed when she developed progressive visual loss. Conclusion: In patients with autoimmune disease, the combination of Azathioprine and steroids rarely cause opportunistic infections. CMV retinitis has not been described before in patients with NMO/NMOSD. This case highlights the importance of neuro ophthalmological assessment in NMO/NMOSD, for early identification of relapses as well as ocular complications of immunosuppression, both of which are sight-threatening.